Acquired methaemoglobinaemia related to phenazopyridine ingestion. (17th September 2012) - Shahani, Lokesh; Sattovia, Stacy
Abstract : Methaemoglobin is an altered state of haemoglobin in which the ferrous ions of haeme are oxidised to the ferric state. This results in increased affinity to the bound oxygen and decreasing its availability to tissues. Most cases of methaemoglobinaemia are acquired, resulting from an increased methaemoglobin formation by various exogenous agents. The authors report an elderly patient presenting to the emergency department with a 1-month history of shortness of breath. Around the same time she had started using over-the-counter (OTC) phenazopyridine tablets for urinary symptoms. The patient was hypoxic and cyanotic; however, lacked evidence of hypoxaemia on the arterial blood gas. The presence of abnormal haemoglobin was suspected and confirmed by elevated levels of methaemoglobin. Phenazopyridine was proposed to be the likely aetiology of the methaemoglobinaemia, which the patient was not aware of. This case highlights the importance of always inquiring the OTC drug use especially in geriatric population.